Preservation of the Ancient Manuscripts of the Book “Waruga Jagat” and the Book “Babad Sumedang” at the Sumedang Pangeran Foundation Library - Ute Lies Khadijah; Yunus Winoto; Rully Khairul Anwar (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2022)
The Pangeran Sumedang Foundation Library is one of the libraries that stores several ancient manuscripts. Ancient manuscripts are a rare type of collection that not everyone, every region, or every library has. Therefore, the existence of a collection of ancient manuscripts needs to be maintained and maintained so that they can be used as a source of information for people who need it. This study aimed to determine preventive and curative ancient manuscript preservation policies and constraints in carrying out ancient manuscript preservation activities at the Pangeran Sumedang Foundation library. While this research tries to examine the preservation of ancient manuscripts, especially the ancient manuscripts of the Waruga Jagat book and the Sumedang chronicle book. The research approach used is a qualitative approach with a case study type.  Based on the results of the research, it is known that the birth of an ancient manuscript preservation policy, especially the ancient manuscript of Kita Waruga Jagat and the Sumedang Chronicle book, is because these two ancient manuscripts have very important informational and historical values regarding the founding of the Sumedang Larang Kingdom. Meanwhile, on the other hand, the manuscript is hundreds of years old and its condition has started to deteriorate, so it is necessary to carry out preservation activities. This preservation activity is carried out using prevention and repair or through a transfer of media forms. Regarding the obstacles in this preservation activity, namely budgetary constraints, limited human resources and limited facilities that support ancient manuscript preservation activities.